Anchoring and electro-optic switching of liquid crystals on nano-structured surfaces fabricated by two-photon based nano-printing - Zhang, Bingru; Plidschun, Malte; Schmidt, Markus A.; Kitzerow, Heinz-Siegfried (Optical Materials Express)
The alignment of liquid crystals on surfaces plays a central role in optimizing their performances. In this work, a cutting-edge nano-lithography-based method to control the local orientation of a thermotropic liquid crystal is applied to easily available commercial standard materials and evaluated. Parallel nanogrooves on a substrate, created through 3D nanoprinting in a negative-tone photoresin optimized for two-photon polymerization are used for this purpose. Azimuthal anchoring energies of the order from 10 −6 J/m 2 to 10 −5 J/m 2 are found, depending on the spacing, width and depth of the grooves. In part, these values are larger than those reported previously for another photopolymer. Both uniform alignment and spatial patterns of different alignment directions can be realized. Electro-optic studies confirm the suitability of the method for electrically addressable photonic applications and indicate strong polar anchoring.
Keywords: Electronic; Optical and Magnetic Materials

Geometric-phase metalens to be used for tunable optical tweezers in microfluidics - Geromel, René; Rennerich, Roman; Zentgraf, Thomas; Kitzerow, Heinz-Siegfried (Liquid Crystals)
Geometric-phase dielectric meta-lenses made of silicon with high numerical aperture and short focal lengths are fabricated and characterised. For circularly polarised light, the same meta-lens can act as a converging or diverging lens, depending on the handedness of the circular polarisation. This effect enables application for optical tweezers that trap or release µm-size polymer beads floating in a microfluidic channel on demand. An electrically addressable polarisation converter based on liquid crystals may be used to switch between the two states of polarisation, at which the light transmitted through the meta-lens is focused (trapping) or defocussed (releasing), respectively.

Luminescent DNA-origami nano-rods dispersed in a lyotropic chromonic liquid crystal - Zhang, Bingru; Nguyen, Linh; Martens, Kevin; Heuer-Jungemann, Amelie; Philipp, Julian; Kempter, Susanne; Rädler, Joachim O.; Liedl, Tim; Kitzerow, Heinz-Siegfried (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

A Comparison of the Most Intense Periods (MIPs) During Competitive Matches and Training Over an 8-Week Period in a Male Elite Field Hockey Team - Büchel, Daniel; Döring, Michael; Baumeister, Jochen (Journal of Science in Sport and Exercise)
Abstract Purpose Wearables serve to quantify the on-court activity in intermittent sports such as field hockey (FH). Based on objective data, benchmarks can be determined to tailor training intensity and volume. Next to average and accumulated values, the most intense periods (MIPs) during competitive FH matches are of special interest, since these quantify the peak intensities players experience throughout the intermittent matches. The aim of this study was to retrospectively compare peak intensities between training and competition sessions in a male FH team competing in the first german division. Methods Throughout an 8-week in-season period, 372 individual activity datasets (144 datasets from competitive sessions) were recorded using the Polar Team Pro sensor (Kempele, Finland). MIPs were calculated applying a rolling window approach with predefined window length (1–5 min) and calculated for Total distance, High-Intensity-Running distance (> 16 km/h), Sprinting distance (> 20 km/h) and Acceleration load. Significant differences between training and competition MIPs were analysed through non-parametric statistical tests ( P < 0.05). Results Analyses revealed higher MIPs during competition for all considered outcomes ( P < 0.001). Effect size estimation revealed strongest effects for sprinting distance ( d = 1.89 to d = 1.22) and lowest effect sizes for acceleration load ( d = 0.92 to d = 0.49). Conclusion The present findings demonstrate that peak intensities during training do not reach those experienced during competitive sessions in a male FH team. Training routines such as manipulations of court-dimensions and team sizes might contribute to this discrepancy. Coaches should compare training and competition intensities to recalibrate training routines to optimize athletes’ preparation for competition.
Keywords: Nutrition and Dietetics; Rehabilitation; Orthopedics and Sports Medicine; Physical Therapy; Sports Therapy and Rehabilitation; Physiology

Structural fingerprints in the reflectance anisotropy of AlInP(001) - Ruiz Alvarado, Isaac Azahel; Zare Pour, Mohammad Amin; Hannappel, Thomas; Schmidt, Wolf Gero (Physical Review B)

On-demand indistinguishable and entangled photons at telecom frequencies using tailored cavity designs - Bauch, David; Siebert, Dustin; Jöns, Klaus; Förstner, Jens; Schumacher, Stefan
The biexciton-exciton emission cascade commonly used in quantum-dot systems to generate polarization entanglement yields photons with intrinsically limited indistinguishability. In the present work we focus on the generation of pairs of photons with high degrees of polarization entanglement and simultaneously high indistinguishibility. We achieve this goal by selectively reducing the biexciton lifetime with an optical resonator. We demonstrate that a suitably tailored circular Bragg reflector fulfills the requirements of sufficient selective Purcell enhancement of biexciton emission paired with spectrally broad photon extraction and two-fold degenerate optical modes. Our in-depth theoretical study combines (i) the optimization of realistic photonic structures solving Maxwell's equations from which model parameters are extracted as input for (ii) microscopic simulations of quantum-dot cavity excitation dynamics with full access to photon properties. We report non-trivial dependencies on system parameters and use the predictive power of our combined theoretical approach to determine the optimal range of Purcell enhancement that maximizes indistinguishability and entanglement to near unity values in the telecom C-band at $1550\,nm$.
Keywords: tet_topic_phc; tet_topic_qd

Zwischen Überwältigung und Beliebigkeit - Wertorientierung im Unterricht als Aufgabe der Lehrpersonenbildung - Schlegel-Matthies, Kirsten (Nachdenken über Lehrerinnen- und Lehrerbildung. Anregungen zur Weiterentwicklung der Pädagogischen Hochschulen in der deutschsprachigen Schweiz. Aus Anlass des 20-Jahre-Jubiläums der Pädagogischen Hochschule Luzern)

Assessment of long-term dietary cadmium exposure in children in Germany: Does consideration of data from total diet studies reduce uncertainties from food monitoring programmes? - Kolbaum, AE; Jung, C; Jaeger, A; Libuda, Lars; Lindtner, O (Food Chem Toxicol)

SEMOK-1-2: Selbstwahrnehmung motorischer Basiskompetenzen in der ersten und zweiten Primarschulklasse. Manual - Bretz, Kathrin; Strotmeyer, Anne; Herrmann, Christian
Um die Selbstwahrnehmung motorischer Basiskompetenzen bei Kindern der 1. und 2. Klasse zu erfassen, wurde ein illustriertes Instrument entwickelt. Das Instrument orientiert sich am MOBAK-1-2 Instrument, mit welchem die motorischen Basiskompetenzen von Kindern getestet werden. Das Manual enthält die Instruktionen sowie die illustrieren Antwortoptionen und Testaufgaben.

Umgang mit Evidenzen angehender Lehrkräfte in den Naturwissenschaften - Epistemologie in der Lehrkräfteausbildung - Pollmeier, Pascal
Eine Forderung nach evidenzbasierter Praxis (EBP) im Bildungswesen kann sowohl vor dem Hintergrund der Bedeutung wissenschaftlicher Evidenzen innerhalb gesellschaftlicher Diskurse als auch der Evidenzbasierung in anderen Bereichen formuliert werden. Der Umgang mit und die Bewertung von Evidenzen stellen somit vor dem Hintergrund epistemologischer Überzeugungen relevante Aufgaben für den Chemieunterricht dar. Dabei ist unklar, inwiefern (angehende) Lehrkräfte über Kompetenzen in EBP verfügen. Bestehende Studien weisen auf einen Bedarf der fachdidaktischen Analyse und Förderung von Kompetenzen in EBP bei angehenden Lehrkräften hin.Im Rahmen dieser Dissertation wurde die Domänenspezifität der Kompetenzen in EBP sowie deren Förderung in einem fachdidaktischen Kontext untersucht. Dabei wurde ein weiterer Schwerpunkt auf den Umgang mit anomalen Beobachtungen im Sinne widersprüchlicher Evidenzen gelegt. Innerhalb von drei Teilstudien wurden unterschiedliche methodische Zugänge zur Kompetenz in EBP auf Grundlage epistemologischer Überzeugungen gewählt.Die Ergebnisse weisen auf einen Förderbedarf der Kompetenz in EBP für angehende Lehrkräfte aller Unterrichtsfächer hin. Eine entwickelte Intervention für angehende Chemielehrkräfte weist eine Wirksamkeit zur Förderung von Kompetenzen in EBP auf. Im Rahmen einer Modellierungsstudie kann der Einfluss von Fachwissen sowie Indizien für einen Einfluss epistemologischer Überzeugungen auf den Umgang mit anomalen Beobachtungen gezeigt werden.
Keywords: Epistemologie; Evidenzen; evidence-based practice

Neue Sorgfaltspflichten für Unternehmen des Agrar- und Ernährungssektors: Empfehlungen zu aktuellen Gesetzesentwicklungen - Spiller, Achim; Nieberg, Hiltrud; Renner, Britta; Balmann, Alfons; Birna, Regina; Bosy-Westphal, Anja; Buyken, Anette; Döring, Thomas; Feindt, Peter; Götz, Kai-Uwe; Linseisen, Jakob; Nöthlings, Ute; et al.
Zitieren als: Wissenschaftlicher Beirat für Agrarpolitik, Ernährung und gesundheitlichen Verbraucher- schutz beim BMEL (2023): Neue Sorgfaltspflichten für Unternehmen des Agrar- und Ernährungssektors: Empfehlungen zu aktuellen Gesetzesentwicklungen. Gutachten. Berlin.

Electrode Potential-Dependent Studies of Protein Adsorption on Ti6Al4V Alloy - Duderija, Belma; González-Orive, Alejandro; Ebbert, Christoph; Neßlinger, Vanessa; Keller, Adrian; Grundmeier, Guido (Molecules)
This article presents the potential-dependent adsorption of two proteins, bovine serum albumin (BSA) and lysozyme (LYZ), on Ti6Al4V alloy at pH 7.4 and 37 °C. The adsorption process was studied on an electropolished alloy under cathodic and anodic overpotentials, compared to the open circuit potential (OCP). To analyze the adsorption process, various complementary interface analytical techniques were employed, including PM-IRRAS (polarization-modulation infrared reflection-absorption spectroscopy), AFM (atomic force microscopy), XPS (X-ray photoelectron spectroscopy), and E-QCM (electrochemical quartz crystal microbalance) measurements. The polarization experiments were conducted within a potential range where charging of the electric double layer dominates, and Faradaic currents can be disregarded. The findings highlight the significant influence of the interfacial charge distribution on the adsorption of BSA and LYZ onto the alloy surface. Furthermore, electrochemical analysis of the protein layers formed under applied overpotentials demonstrated improved corrosion protection properties. These studies provide valuable insights into protein adsorption on titanium alloys under physiological conditions, characterized by varying potentials of the passive alloy.
Keywords: Chemistry (miscellaneous); Analytical Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Molecular Medicine; Drug Discovery; Pharmaceutical Science

Electropolymerization of acrylic acid on steel for enhanced joining by plastic deformation - Duderija, B.; Sahin, F.; Meinderink, D.; Calderón-Gómez, J.C.; Schmidt, H.C.; Homberg, W.; Grundmeier, G.; González-Orive, A. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Gesundheitsmanagement: Gesunde Mitarbeiter - gesunder Betrieb? - Meier, Heiko; Sennefelder, Lisa (markt&wirtschaft)

Sportliche Angebote zur Förderung von Vertrauen in öffentlichen Verwaltungen - Sennefelder, Lisa

Chirped Bloch-harmonic oscillations in a parametrically forced optical lattice - Ali, Usman; Holthaus, Martin; Meier, Torsten (Physical Review Research)
Keywords: General Physics and Astronomy

Chirped Bloch-harmonic oscillations in a parametrically forced optical lattice - Meier, Torsten

Rezension zu: Bette, K.-H. & Kühnle, F.: Flitzer im Sport – Zur Sozialfigur des Störenfrieds - Sennefelder, Lisa (Sport und Gesellschaft)

Electronic Structure and Excited-State Dynamics of the NIR-II Emissive Molybdenum(III) Analogue to the Molecular Ruby - Kitzmann, Winald R.; Hunger, David; Reponen, Antti-Pekka M.; Förster, Christoph; Schoch, Roland; Bauer, Matthias; Feldmann, Sascha; van Slageren, Joris; Heinze, Katja (Inorganic Chemistry)
Photoactive chromium(III) complexes saw a conceptual breakthrough with the discovery of the prototypical molecular ruby mer-[Cr(ddpd)2]3+ (ddpd = N,N′-dimethyl-N,N′-dipyridin-2-ylpyridine-2,6-diamine), which shows intense long-lived near-infrared (NIR) phosphorescence from metal-centered spin-flip states. In contrast to the numerous studies on chromium(III) photophysics, only 10 luminescent molybdenum(III) complexes have been reported so far. Here, we present the synthesis and characterization of mer-MoX3(ddpd) (1, X = Cl; 2, X = Br) and cisfac-[Mo(ddpd)2]3+ (cisfac-[3]3+), an isomeric heavy homologue of the prototypical molecular ruby. For cisfac-[3]3+, we found strong zero-field splitting using magnetic susceptibility measurements and electron paramagnetic resonance spectroscopy. Electronic spectra covering the spin-forbidden transitions show that the spin-flip states in mer-1, mer-2, and cisfac-[3]3+ are much lower in energy than those in comparable chromium(III) compounds. While all three complexes show weak spin-flip phosphorescence in NIR-II, the emission of cisfac-[3]3+ peaking at 1550 nm is particularly low in energy. Femtosecond transient absorption spectroscopy reveals a short excited-state lifetime of 1.4 ns, 6 orders of magnitude shorter than that of mer-[Cr(ddpd)2]3+. Using density functional theory and ab initio multireference calculations, we break down the reasons for this disparity and derive principles for the design of future stable photoactive molybdenum(III) complexes.
Keywords: Inorganic Chemistry; Physical and Theoretical Chemistry

Chemical and photophysical properties of amine functionalized bis‐NHC‐pyridine‐RuII complexes - Fritsch, Lorena; Vukadinovic, Yannik; Lang, Moritz; Naumann, Robert; Bertrams, Maria-Sophie; Kruse, Ayla; Schoch, Roland; Müller, Patrick; Neuba, Adam; Dierks, Philipp; Lochbrunner, Stefan; Kerzig, Christoph; et al. (ChemPhotoChem)
The effects of backbone amine functionalization in three new homoleptic C^N^C type ruthenium(II) complexes bearing a tridentate bis‐imidazole‐2‐ylidene pyridine ligand framework are characterized and studied by single crystal diffraction, electrochemistry, optical spectroscopy and transient absorption spectroscopy in combination with ab initio DFT calculations. Functionalization by dimethylamine groups in 4‐position of the pyridine backbone significantly influences the properties of the complexes as revealed by comparison with the unfunctionalized references. As a result of the amine functionalization, a higher molar absorption coefficient of the MLCT bands, a decreased photoluminescence quantum yield at room temperature together with a shortened excited state lifetime but an improved photostability is observed. Introduction of electron donating and withdrawing groups at the NHC unit modifies the electronic and optical properties, such as the oxidation potential, absorption and emission properties, and the lifetimes of the excited states.
Keywords: Organic Chemistry; Physical and Theoretical Chemistry; Analytical Chemistry; Computing Resources Provided by the Paderborn Center for Parallel Computing; pc2-ressources

Auswirkungen einer Online-Intervention (Mindset, Lerntechniken) auf den Studieneinstieg - Diederich, Malte; Spatz, Verena; Bauer, Anna Brigitte (Phydid B, Didaktik der Physik, Beiträge zur DPG-Frühjahrstagung (2022))

Quo Vadis CO2 Activation: Catalytic Reduction of CO2 to Methanol Using Aluminum and Gallium/Carbon‐based Ambiphiles - Krämer, Felix; Paradies, Jan; Fernández, Israel; Breher, Frank (Chemistry – A European Journal)
Abstract We report on so‐called “hidden FLPs” (FLP: frustrated Lewis pair) consisting of a phosphorus ylide featuring a group 13 fragment in the ortho position of a phenyl ring scaffold to form five‐membered ring structures. Although the formation of the Lewis acid/base adducts was observed in the solid state, most of the title compounds readily react with carbon dioxide to provide stable insertion products. Strikingly, 0.3–3.0 mol% of the reported aluminum and gallium/carbon‐based ambiphiles catalyze the reduction of CO 2 to methanol with satisfactory high selectivity and yields using pinacol borane as stoichiometric reduction equivalent. Comprehensive computational studies provided valuable mechanistic insights and shed more light on activity differences.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Antimicrobial Brushes on Titanium via “Grafting to” Using Phosphonic Acid/Pyridinium Containing Block Copolymers - Methling, Rafael; Dückmann, Oliver; Simon, Frank; Wolf‐Brandstetter, Cornelia; Kuckling, Dirk (Macromolecular Materials and Engineering)
Abstract Coating medical implants with antibacterial polymers may prevent postoperative infections which are a common issue for conventional titanium implants and can even lead to implant failure. Easily applicable diblock copolymers are presented that form polymer brushes via “grafting to” mechanism on titanium and equip the modified material with antibacterial properties. The polymers carry quaternized pyridinium units to combat bacteria and phosphonic acid groups which allow the linear chains to be anchored to metal surfaces in a convenient coating process. The polymers are synthesized via reversible‐addition‐fragmentation‐chain‐transfer (RAFT) polymerization and postmodifications and are characterized using NMR spectroscopy and SEC. Low grafting densities are a major drawback of the “grafting to” approach compared to “grafting from”. Thus, the number of phosphonic acid groups in the anchor block are varied to investigate and optimize the surface binding. Modified titanium surfaces are examined regarding their composition, wetting behavior, streaming potential, and coating stability. Evaluation of the antimicrobial properties revealed reduced bacterial adhesion and biofilm formation for certain polymers, albeit the cell biocompatibility against human gingival fibroblasts is also impaired. The presented findings show the potential of easy‐to‐apply polymer coatings and aid in designing next‐generation implant surface modifications.
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry; General Chemical Engineering

Polymeric Networks Containing Amine Derivatives as Organocatalysts for Knoevenagel Reaction within Continuously Driven Microfluidic Reactors - Killi, Naresh; Bartenbach, Julian; Kuckling, Dirk (Gels)
The Knoevenagel reaction is a classic reaction in organic chemistry for the formation of C-C bonds. In this study, various catalytic monomers for Knoevenagel reactions were synthesized and polymerized via photolithography to form polymeric gel dots with a composition of 90% catalyst, 9% gelling agent and 1% crosslinker. Furthermore, these gel dots were inserted into a microfluidic reactor (MFR) and the conversion of the reaction using gel dots as catalysts in the MFR for 8 h at room temperature was studied. The gel dots containing primary amines showed a better conversion of about 83–90% with aliphatic aldehyde and 86–100% with aromatic aldehyde, compared to the tertiary amines (52–59% with aliphatic aldehyde and 77–93% with aromatic aldehydes) which resembles the reactivity of the amines. Moreover, the addition of polar solvent (water) in the reaction mixture and the swelling properties of the gel dots by altering the polymer backbone showed a significant enhancement in the conversion of the reaction, due to the increased accessibility of the catalytic sites in the polymeric network. These results suggested the primary-amine-based catalysts facilitate better conversion compared to tertiary amines and the reaction solvent had a significant influence on organocatalysis to improve the efficiency of MFR.
Keywords: Knoevenagel reaction; organocatalysis; polymeric gel dots; microfluidic reactions; polymeric networks

Investigations of Ni-based methanation catalysts under dynamic conditions via hard X-ray spectroscopy - Strübbe, Sven
Im Rahmen dieser Dissertation wurden Katalysatoren, welche auf der thermischen Zersetzung von metallorganischen Gerüstverbindungen basieren, mittels Röntgenabsorptionsspektroskopie (XAS) und Röntgenemissionsspektroskopie (XES) untersucht. Durch diesen synthetischen Ansatz können hochdisperse Ni-basierte Katalysatoren eingebettet in einer Kohlenstoffmatrix gewonnen werden, welche für die Methanisierung von CO2 Einsatz finden. Diese sollen eine hohe Stabilität gegenüber Wasserstoffausfällen aufweisen, welche bedingt durch Wetterfluktuationen in der Gewinnung von grünem Wasserstoff auftreten. Um ein derartiges System gezielt gestalten zu können, ist ein detailliertes Verständnis zugrundeliegender chemischer Mechanismen und damit einhergehend elektronischer Strukturen der Katalysatorsysteme notwendig. Durch die detaillierte Analyse der Katalysator-Vorstufen mittels XAS konnte gezeigt werden, dass auch unter reduktiven Bedingungen in der thermischen Zersetzung Spuren von Ni(II) vorliegen und keine reine Nifcc-Struktur erreicht werden konnte. Eine detaillierte Auswertung der gleichen Präkatalysatoren mittels XES konnte durch eine neuartige Kombination von HERFD-XANES, theoretischer Berechnungen und VtC-XES einen eindeutigen Beweis für das Vorhandensein der gewünschten Kohlenstoffmatrix sowie Spuren von NiO im Präkatalysator liefern, welche sich vorteilhaft auf die spätere Aktivität im finalen Katalysator auswirken. Abschließend konnte mittels einer in-situ Untersuchung der Temperaturbereich, in dem sich die aktive Katalysatorspezies ausbildet, auf 80 bis 200 C eingegrenzt werden. Schließlich konnte ein eindeutiger Zusammenhang zwischen dem Verlust einer stabilisierenden Kohlenstoffschicht und einem Rückgang der Aktivität belegt werden.

Nonlinear Dielectric Geometric-Phase Metasurface with Simultaneous Structure and Lattice Symmetry Design - Liu, Bingyi; Geromel, René; Su, Zhaoxian; Guo, Kai; Wang, Yongtian; Guo, Zhongyi; Huang, Lingling; Zentgraf, Thomas (ACS Photonics)
In this work, we utilize thin dielectric meta-atoms placed on a silver substrate to efficiently enhance and manipulate the third-harmonic generation. We theoretically and experimentally reveal that when the structural symmetry of the meta-atom is incompatible with the lattice symmetry of an array, some generalized nonlinear geometric phases appear, which offers new possibilities for harmonic generation control beyond the accessible symmetries governed by the selection rule. The underlying mechanism is attributed to the modified rotation of the effective principal axis of a dense meta-atom array, where the strong coupling among the units gives rise to a generalized linear geometric phase modulation of the pump light. Therefore, nonlinear geometric phases carried by third-harmonic emissions are the natural result of the wave-mixing process among the modes excited at the fundamental frequency. This mechanism further points out a new strategy to predict the nonlinear geometric phases delivered by the nanostructures according to their linear responses. Our design is simple and efficient and offers alternatives for the nonlinear meta-devices that are capable of flexible photon generation and manipulation.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Biotechnology; Electronic; Optical and Magnetic Materials

Einsatzmöglichkeiten von digitalen Medien im Physikunterricht - eine Übersicht - Weiler, David; Burde , Jan-Philipp; Große-Heilmann, Rike Isabel; Riese, Josef; Schubatzky, Thomas (Plus Lucis)

Alterations of postural control across the menstrual cycle – A systematic review - Pohle, Carina; Becker, Linda; Baumeister, Jochen (Gait & Posture)
Keywords: Rehabilitation; Orthopedics and Sports Medicine; Biophysics

Macrocyclization of Dienes under Confinement with Cationic Tungsten Imido/Oxo Alkylidene N‐Heterocyclic Carbene Complexes - Ziegler, Felix; Bruckner, Johanna R.; Nowakowski, Michał; Bauer, Matthias; Probst, Patrick; Atwi, Boshra; Buchmeiser, Michael R. (ChemCatChem)
Macrocyclization reactions are still challenging due to competing oligomerization, which requires the use of small substrate concentrations. Here, the cationic tungsten imido and tungsten oxo alkylidene N-heterocyclic carbene complexes [[W(N-2,6-Cl2-C6H3)(CHCMe2Ph(OC6F5)(pivalonitrile)(IMes)+ B(ArF)4−] (W1) and [W(O)(CHCMe2Ph(OCMe(CF3)2)(IMes)(CH3CN)+ B(ArF)4−] (W2) (IMes=1,3-dimesitylimidazol-2-ylidene; B(ArF)4−=tetrakis(3,5-bis(trifluoromethyl)phenyl borate) have been immobilized inside the pores of ordered mesoporous silica (OMS) with pore diameters of 3.3 and 6.8 nm, respectively, using a pore-selective immobilization protocol. X-ray absorption spectroscopy of W1@OMS showed that even though the catalyst structure is contracted due to confinement by the mesopores, both the oxidation state and structure of the catalyst stayed intact upon immobilization. Catalytic testing with four differently sized α,ω-dienes revealed a dramatically increased macrocyclization (MC) and Z-selectivity of the supported catalysts compared to the homogenous progenitors, allowing high substrate concentrations of 25 mM. With the supported complexes, a maximum increase in MC-selectivity from 27 to 81 % and in Z-selectivity from 17 to 34 % was achieved. In general, smaller mesopores exhibited a stronger confinement effect. A comparison of the two supported tungsten-based catalysts showed that W1@OMS possesses a higher MC-selectivity, while W2@OMS exhibits a higher Z-selectivity which can be rationalized by the structures of the catalysts.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Catalysis

Broadband Mie scattering effects by structural features of setae from the Saharan silver ant Cataglyphis bombycina - Schwind, Bertram; Wu, Xia; Tiemann, Michael; Fabritius, Helge-Otto (Journal of the Optical Society of America B)
The Saharan desert ant Cataglyphis bombycina is densely covered with shiny silver setae (hair-like structures). Their appearance was explained by geometric optics and total internal reflection. The setae also increase the emissivity of the ant, as they form an effective medium. This work provides additional data on microstructural details of the setae that are used to simulate the scattering of an individual seta to explain their influence on the optical properties. This is achieved by characterization of their structure using light microscopy and scanning/transmission electron microscopy. How the microstructural features influence scattering is investigated wave-optically within the limits of finite-difference time-domain simulations from the ultraviolet to the mid-infrared spectral range to elucidate the optical effects beyond ray optics and effective medium theory. The results show that Mie scattering plays an important role in protecting the ant from solar radiation and could be relevant for its thermal tolerance.
Keywords: Atomic and Molecular Physics; and Optics; Statistical and Nonlinear Physics

Electric-field-induced second harmonic generation in silicon dioxide - Widhalm, Alex; Golla, Christian; Weber, Nils; Mackwitz, Peter; Zrenner, Artur; Meier, Cedrik (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Fachliche und überfachliche Herausforderungen in der Studieneingangsphase Physik - Bauer, Anna; Woitkowski, David; Reuter, Dirk; Reinhold, Peter (Hochschullehre erforschen.)
Die Studieneingangsphase Physik stellt für die Studienanfänger Innen einen komplexen Lernprozess mit vielfältigen Anforderungen auf fachlicher, Metakognitions- und Sozialisations-Ebene dar, der ihre akademische Identitätsbildung beeinflusst und prägt. Ziel des Projektes Paderborner Studieneingangsphase Physik (PSΦ) ist die evidenzbasierte Gestaltung eines strukturierten Studieneinstiegs und einer in sich kohärent abgestimmten Studieneingangsphase „aus einem Guss“. Die Implementation eines neuen Übungsformats (Präsenzübungen) in den Fachvorlesungen sowie die Unterstützung der Studierenden im Bereich des selbstregulierten Lernens zeigen positive Effekte in einer erhöhten Teilnahmequote sowie Zufriedenheit der Studierenden mit der Veranstaltung, in einem aktiveren Arbeitsverhalten sowie einer höheren Bestehensquote der Klausur. Ein messbar größerer Fachwissenserwerb konnte nicht nachgewiesen werden. Auf Basis der Evidenzen konnten Stellschrauben für die Weiterentwicklung sowie für die Unterstützung der Lehrenden abgeleitet werden. In dem Beitrag werden die Gelingensbedingungen und Strukturen für eine wirksame Zusammenarbeit von Fachdidaktik und Fachwissenschaft am Beispiel der Überarbeitung der Studieneingangsphase im Rahmen einer community of practice sowie der Wirksamkeit der Implementierung diskutiert.

A Versatile Metasurface Enabling Superwettability for Self‐Cleaning and Dynamic Color Response - Lu, Jinlong; Sain, Basudeb; Georgi, Philip; Protte, Maximilian; Bartley, Tim; Zentgraf, Thomas (Advanced Optical Materials)
Metasurfaces provide applications for a variety of flat elements and devices due to the ability to modulate light with subwavelength structures. The working principle meanwhile gives rise to the crucial problem and challenge to protect the metasurface from dust or clean the unavoidable contaminants during daily usage. Here, taking advantage of the intelligent bioinspired surfaces which exhibit self-cleaning properties, a versatile dielectric metasurface benefiting from the obtained superhydrophilic or quasi-superhydrophobic states is shown. The design is realized by embedding the metasurface inside a large area of wettability supporting structures, which is highly efficient in fabrication, and achieves both optical and wettability functionality at the same time. The superhydrophilic state enables an enhanced optical response with water, while the quasi-superhydrophobic state imparts the fragile antennas an ability to self-clean dust contamination. Furthermore, the metasurface can be easily switched and repeated between these two wettability or functional states by appropriate treatments in a repeatable way, without degrading the optical performance. The proposed design strategy will bring new opportunities to smart metasurfaces with improved optical performance, versatility, and physical stability.

Salting-Out of DNA Origami Nanostructures by Ammonium Sulfate - Hanke, Marcel; Hansen, Niklas; Chen, Ruiping; Grundmeier, Guido; Fahmy, Karim; Keller, Adrian (International Journal of Molecular Sciences)
DNA origami technology enables the folding of DNA strands into complex nanoscale shapes whose properties and interactions with molecular species often deviate significantly from that of genomic DNA. Here, we investigate the salting-out of different DNA origami shapes by the kosmotropic salt ammonium sulfate that is routinely employed in protein precipitation. We find that centrifugation in the presence of 3 M ammonium sulfate results in notable precipitation of DNA origami nanostructures but not of double-stranded genomic DNA. The precipitated DNA origami nanostructures can be resuspended in ammonium sulfate-free buffer without apparent formation of aggregates or loss of structural integrity. Even though quasi-1D six-helix bundle DNA origami are slightly less susceptible toward salting-out than more compact DNA origami triangles and 24-helix bundles, precipitation and recovery yields appear to be mostly independent of DNA origami shape and superstructure. Exploiting the specificity of ammonium sulfate salting-out for DNA origami nanostructures, we further apply this method to separate DNA origami triangles from genomic DNA fragments in a complex mixture. Our results thus demonstrate the possibility of concentrating and purifying DNA origami nanostructures by ammonium sulfate-induced salting-out.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Second Harmonic Optical Circular Dichroism of Plasmonic Chiral Helicoid-III Nanoparticles - Spreyer, Florian; Mun, Jungho; Kim, Hyeohn; Kim, Ryeong Myeong; Nam, Ki Tae; Rho, Junsuk; Zentgraf, Thomas (ACS Photonics)
While plasmonic particles can provide optical resonances in a wide spectral range from the lower visible up to the near-infrared, often, symmetry effects are utilized to obtain particular optical responses. By breaking certain spatial symmetries, chiral structures arise and provide robust chiroptical responses to these plasmonic resonances. Here, we observe strong chiroptical responses in the linear and nonlinear optical regime for chiral L-handed helicoid-III nanoparticles and quantify them by means of an asymmetric factor, the so-called g-factor. We calculate the linear optical g-factors for two distinct chiroptical resonances to −0.12 and –0.43 and the nonlinear optical g-factors to −1.45 and −1.63. The results demonstrate that the chirality of the helicoid-III nanoparticles is strongly enhanced in the nonlinear regime.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Biotechnology; Electronic; Optical and Magnetic Materials

Nonlinear down-conversion in a single quantum dot - Jonas, B.; Heinze, D.; Schöll, E.; Kallert, P.; Langer, T.; Krehs, S.; Widhalm, A.; Jöns, K. D.; Reuter, D.; Schumacher, S.; Zrenner, Artur (Nature Communications)
Abstract Tailored nanoscale quantum light sources, matching the specific needs of use cases, are crucial building blocks for photonic quantum technologies. Several different approaches to realize solid-state quantum emitters with high performance have been pursued and different concepts for energy tuning have been established. However, the properties of the emitted photons are always defined by the individual quantum emitter and can therefore not be controlled with full flexibility. Here we introduce an all-optical nonlinear method to tailor and control the single photon emission. We demonstrate a laser-controlled down-conversion process from an excited state of a semiconductor quantum three-level system. Based on this concept, we realize energy tuning and polarization control of the single photon emission with a control-laser field. Our results mark an important step towards tailored single photon emission from a photonic quantum system based on quantum optical principles.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry

Pulse shaping for on-demand emission of single Raman photons from a quantum-dot biexciton - Praschan, Tom; Heinze, Dirk; Breddermann, Dominik; Zrenner, Artur; Walther, Andrea; Schumacher, Stefan (Physical Review B)

Size‐Dependent Strain Relaxation in InAs Quantum Dots on Top of GaAs(111)A Nanopillars - Riedl, Thomas; Kunnathully, Vinay S.; Trapp, Alexander; Langer, Timo; Reuter, Dirk; Lindner, Jörg K. N. (Advanced Materials Interfaces)
Keywords: Mechanical Engineering; Mechanics of Materials

Giant Photoelasticity of Polaritons for Detection of Coherent Phonons in a Superlattice with Quantum Sensitivity - Kobecki, Michal; Scherbakov, Alexey V.; Kukhtaruk, Serhii M.; Yaremkevich, Dmytro D.; Henksmeier, Tobias; Trapp, Alexander; Reuter, Dirk; Gusev, Vitalyi E.; Akimov, Andrey V.; Bayer, Manfred (Physical Review Letters)
Keywords: General Physics and Astronomy

Ammonium enables reversible aqueous Zn battery chemistries by tailoring the interphase - Ma, Lin; Pollard, Travis P.; Zhang, Yong; Schroeder, Marshall A.; Ren, Xiaoming; Han, Kee Sung; Ding, Michael S.; Cresce, Arthur V.; Atwater, Terrill B.; Mars, Julian; Cao, Longsheng; Steinrück, Hans-Georg; et al. (One Earth)
Keywords: Earth and Planetary Sciences (miscellaneous); General Environmental Science

Conformal Pressure and Fast-Charging Li-Ion Batteries - Cao, Chuntian; Steinrück, Hans-Georg; Paul, Partha P; Dunlop, Alison R.; Trask, Stephen E.; Jansen, Andrew; Kasse, Robert M; Thampy, Vivek; Yusuf, Maha; Nelson Weker, Johanna; Shyam, Badri; Subbaraman, Ram; et al. (Journal of The Electrochemical Society)
Abstract Batteries capable of extreme fast-charging (XFC) are a necessity for the deployment of electric vehicles. Material properties of electrodes and electrolytes along with cell parameters such as stack pressure and temperature have coupled, synergistic, and sometimes deleterious effects on fast-charging performance. We develop a new experimental testbed that allows precise and conformal application of electrode stack pressure. We focus on cell capacity degradation using single-layer pouch cells with graphite anodes, LiNi0.5Mn0.3Co0.2O2 (NMC532) cathodes, and carbonate-based electrolyte. In the tested range (10 – 125 psi), cells cycled at higher pressure show higher capacity and less capacity fading. Additionally, Li plating decreases with increasing pressure as observed with scanning electron microscopy (SEM) and optical imaging. While the loss of Li inventory from Li plating is the largest contributor to capacity fade, electrochemical and SEM examination of the NMC cathodes after XFC experiments show increased secondary particle damage at lower pressure. We infer that the better performance at higher pressure is due to more homogenous reactions of active materials across the electrode and less polarization through the electrode thickness. Our study emphasizes the importance of electrode stack pressure in XFC batteries and highlights its subtle role in cell conditions.
Keywords: Materials Chemistry; Electrochemistry; Surfaces; Coatings and Films; Condensed Matter Physics; Renewable Energy; Sustainability and the Environment; Electronic; Optical and Magnetic Materials

Corrosion fatigue behavior of electron beam melted iron in simulated body fluid - Wackenrohr, Steffen; Torrent, Christof Johannes Jaime; Herbst, Sebastian; Nürnberger, Florian; Krooss, Philipp; Ebbert, Christoph; Voigt, Markus; Grundmeier, Guido; Niendorf, Thomas; Maier, Hans Jürgen (npj Materials Degradation)
Abstract Pure iron is very attractive as a biodegradable implant material due to its high biocompatibility. In combination with additive manufacturing, which facilitates great flexibility of the implant design, it is possible to selectively adjust the microstructure of the material in the process, thereby control the corrosion and fatigue behavior. In the present study, conventional hot-rolled (HR) pure iron is compared to pure iron manufactured by electron beam melting (EBM). The microstructure, the corrosion behavior and the fatigue properties were studied comprehensively. The investigated sample conditions showed significant differences in the microstructures that led to changes in corrosion and fatigue properties. The EBM iron showed significantly lower fatigue strength compared to the HR iron. These different fatigue responses were observed under purely mechanical loading as well as with superimposed corrosion influence and are summarized in a model that describes the underlying failure mechanisms.
Keywords: Materials Chemistry; Materials Science (miscellaneous); Chemistry (miscellaneous); Ceramics and Composites

Oxide Modified Iron in Electron Beam Powder Bed Fusion—From Processability to Corrosion Properties - Torrent, Christof J. J.; Krooß, Philipp; Huang, Jingyuan; Voigt, Markus; Ebbert, Christoph; Knust, Steffen; Grundmeier, Guido; Niendorf, Thomas (Alloys)
Additive manufacturing (AM) processes are not solely used where maximum design freedom meets low lot sizes. Direct microstructure design and topology optimization can be realized concomitantly during processing by adjusting the geometry, the material composition, and the solidification behavior of the material considered. However, when complex specific requirements have to be met, a targeted part design is highly challenging. In the field of biodegradable implant surgery, a cytocompatible material of an application-adapted shape has to be characterized by a specific degradation behavior and reliably predictable mechanical properties. For instance, small amounts of oxides can have a significant effect on microstructural development, thus likewise affecting the strength and corrosion behavior of the processed material. In the present study, biocompatible pure Fe was processed using electron powder bed fusion (E-PBF). Two different modifications of the Fe were processed by incorporating Fe oxide and Ce oxide in different proportions in order to assess their impact on the microstructural evolution, the mechanical response and the corrosion behavior. The quasistatic mechanical and chemical properties were analyzed and correlated with the final microstructural appearance.

Efficient Frequency Conversion with Geometric Phase Control in Optical Metasurfaces - Reineke Matsudo, Bernhard; Sain, Basudeb; Carletti, Luca; Zhang, Xue; Gao, Wenlong; Angelis, Costantino; Huang, Lingling; Zentgraf, Thomas (Advanced Science)
Keywords: General Physics and Astronomy; General Engineering; Biochemistry; Genetics and Molecular Biology (miscellaneous); General Materials Science; General Chemical Engineering; Medicine (miscellaneous)

Spin-Orbit Interaction of Light Enabled by Negative Coupling in High-Quality-Factor Optical Metasurfaces - Gao, Wenlong; Sain, Basudeb; Zentgraf, Thomas (Physical Review Applied)
Keywords: General Physics and Astronomy

Environment‐Dependent Stability and Mechanical Properties of DNA Origami Six‐Helix Bundles with Different Crossover Spacings - Xin, Yang; Piskunen, Petteri; Suma, Antonio; Li, Changyong; Ijäs, Heini; Ojasalo, Sofia; Seitz, Iris; Kostiainen, Mauri A.; Grundmeier, Guido; Linko, Veikko; Keller, Adrian (Small)
Keywords: Biomaterials; Biotechnology; General Materials Science; General Chemistry

Remote epitaxy of InxGa1-xAs (0 0 1) on graphene covered GaAs(0 0 1) substrates - Henksmeier, T.; Schulz, J.F.; Kluth, E.; Feneberg, M.; Goldhahn, R.; Sanchez, A.M.; Voigt, M.; Grundmeier, Guido; Reuter, Dirk (Journal of Crystal Growth)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

Reversible functionalization and exfoliation of graphite by a Diels–Alder reaction with furfuryl amine - Filvan Torkaman, Najmeh; Kley, Marina; Bremser, Wolfgang; Wilhelm, René (RSC Advances)
Furfuryl amine-functionalized few-layered graphene was prepared via a mechanochemical process by a [4 + 2] cycloaddition under solvent-free conditions.
Keywords: General Chemical Engineering; General Chemistry

Influence of hydrogel coatings on corrosion and fatigue of iron in simulated body fluid - Huang, Jingyuan; Voigt, Markus; Wackenrohr, Steffen; Ebbert, Christoph; Keller, Adrian; Maier, Hans Jürgen; Grundmeier, Guido (Materials and Corrosion)
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry

Increased Cognitive Demands Affect Agility Performance in Female Athletes - Implications for Testing and Training of Agility in Team Ball Sports - Büchel, Daniel; Gokeler, Alli; Heuvelmans, Pieter; Baumeister, Jochen (Perceptual and Motor Skills)
Agility, a key component of team ball sports, describes an athlete´s ability to move fast in response to changing environments. While agility requires basic cognitive functions like processing speed, it also requires more complex cognitive processes like working memory and inhibition. Yet, most agility tests restrict an assessment of cognitive processes to simple reactive times that lack ecological validity. Our aim in this study was to assess agility performance by means of total time on two agility tests with matched motor demands but with both low and high cognitive demands. We tested 22 female team athletes on SpeedCourt, using a simple agility test (SAT) that measured only processing speed and a complex agility test (CAT) that required working memory and inhibition. We found excellent to good reliability for both our SAT (ICC = .79) and CAT (ICC =.70). Lower agility performance on the CAT was associated with increased agility total time and split times ( p < .05). These results demonstrated that agility performance depends on the complexity of cognitive demands. There may be interference-effects between motor and cognitive performances, reducing speed when environmental information becomes more complex. Future studies should consider agility training models that implement complex cognitive stimuli to challenge athletes according to competitive demands. This will also allow scientists and practitioners to tailor tests to talent identification, performance development and injury rehabilitation.
Keywords: Sensory Systems; Experimental and Cognitive Psychology

Effect of Surface Hydrophobicity on the Adsorption of a Pilus-Derived Adhesin-like Peptide - Yang, Yu; Huang, Jingyuan; Dornbusch, Daniel; Grundmeier, Guido; Fahmy, Karim; Keller, Adrian; Cheung, David L. (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Time-Dependent DNA Origami Denaturation by Guanidinium Chloride, Guanidinium Sulfate, and Guanidinium Thiocyanate - Hanke, Marcel; Hansen, Niklas; Tomm, Emilia; Grundmeier, Guido; Keller, Adrian (International Journal of Molecular Sciences)
Guanidinium (Gdm) undergoes interactions with both hydrophilic and hydrophobic groups and, thus, is a highly potent denaturant of biomolecular structure. However, our molecular understanding of the interaction of Gdm with proteins and DNA is still rather limited. Here, we investigated the denaturation of DNA origami nanostructures by three Gdm salts, i.e., guanidinium chloride (GdmCl), guanidinium sulfate (Gdm2SO4), and guanidinium thiocyanate (GdmSCN), at different temperatures and in dependence of incubation time. Using DNA origami nanostructures as sensors that translate small molecular transitions into nanostructural changes, the denaturing effects of the Gdm salts were directly visualized by atomic force microscopy. GdmSCN was the most potent DNA denaturant, which caused complete DNA origami denaturation at 50 °C already at a concentration of 2 M. Under such harsh conditions, denaturation occurred within the first 15 min of Gdm exposure, whereas much slower kinetics were observed for the more weakly denaturing salt Gdm2SO4 at 25 °C. Lastly, we observed a novel non-monotonous temperature dependence of DNA origami denaturation in Gdm2SO4 with the fraction of intact nanostructures having an intermediate minimum at about 40 °C. Our results, thus, provide further insights into the highly complex Gdm–DNA interaction and underscore the importance of the counteranion species.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Return to play in elite rugby players after severe knee injuries - Robyn, Aneurin D.; Louw, Quinette A.; Baumeister, Jochen (South African Journal of Physiotherapy)
Background: Medical professionals working in an elite sport environment have the challenging task to balance the athlete’s readiness to return to the playing field after severe injury with other stakeholders’ (coaches, sponsors, teammates) opinions and objectives.Objectives: Our study aimed to evaluate differences in the physical profiles of elite rugby players at return to play (RTP) after a severe knee injury, compared with their pre-injury profiles and matched controls.Method: Before the injury, participants performed four performance tests during their preseason screening. These tests were repeated and compared to baseline once a player was declared fit to play.Results: Significant differences (p ≤ 0.05) were found in the injured players’ group who were slower over 10 m speed, in their decision-making time and the total time of the reactive agility tests at RTP, whilst controls were significantly faster over 10 m and 30 m speed tests. The countermovement jump outcomes showed significant improvement in the uninjured participants (p ≤ 0.05).Conclusion: Our study highlights that injured players’ running speeds and decision-making times are slower after injury. The uninjured players have a positive outcome to training and match stimulus by improving their running speed and lower body explosive power during the season.Clinical implications: Our study provides insight into the RTP profile of elite rugby players, and a novel finding was the decision-making time deficit. This highlights the importance of cognitive training during injury rehabilitation as athletes make numerous decisions in a pressured and uncontrolled environment during a match. Speed training development is recommended as the athletes were slower after severe knee injury.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation

Psychological readiness of elite rugby players at return to play after severe knee injury - Robyn, A.D.; Louw, Q.A.; Baumeister, Jochen (African Journal for Physical Activity and Health Sciences (AJPHES))
Keywords: General Medicine

Multimodal quantification of degradation pathways during extreme fast charging of lithium-ion batteries - McShane, Eric J.; Paul, Partha P.; Tanim, Tanvir R.; Cao, Chuntian; Steinrück, Hans-Georg; Thampy, Vivek; Trask, Stephen E.; Dunlop, Alison R.; Jansen, Andrew N.; Dufek, Eric J.; Toney, Michael F.; Weker, Johanna Nelson; et al. (Journal of Materials Chemistry A)
Using a unique combination of advanced characterization techniques, we identify specific degradation mechanisms and quantify degradative species formed during fast charge cycling of lithium-ion battery pouch cells.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Simultaneous neutron and X-ray tomography for visualization of graphite electrode degradation in fast-charged lithium-ion batteries - Yusuf, Maha; LaManna, Jacob M.; Paul, Partha P.; Agyeman-Budu, David N.; Cao, Chuntian; Dunlop, Alison R.; Jansen, Andrew N.; Polzin, Bryant J.; Trask, Stephen E.; Tanim, Tanvir R.; Dufek, Eric J.; Thampy, Vivek; et al. (Cell Reports Physical Science)
Keywords: General Physics and Astronomy; General Energy; General Engineering; General Materials Science; General Chemistry

Asymmetric parametric generation of images with nonlinear dielectric metasurfaces - Kruk, Sergey S.; Wang, Lei; Sain, Basudeb; Dong, Zhaogang; Yang, Joel; Zentgraf, Thomas; Kivshar, Yuri (Nature Photonics)
Subwavelength dielectric resonators assembled into metasurfaces have become a versatile tool for miniaturizing optical components approaching the nanoscale. An important class of metasurface functionalities is associated with asymmetry in both the generation and transmission of light with respect to reversals of the positions of emitters and receivers. The nonlinear light–matter interaction in metasurfaces offers a promising pathway towards miniaturization of the asymmetric control of light. Here we demonstrate asymmetric parametric generation of light in nonlinear metasurfaces. We assemble dissimilar nonlinear dielectric resonators into translucent metasurfaces that produce images in the visible spectral range on being illuminated by infrared radiation. By design, the metasurfaces produce different and completely independent images for the reversed direction of illumination, that is, when the positions of the infrared emitter and the visible light receiver are exchanged. Nonlinearity-enabled asymmetric control of light by subwavelength resonators paves the way towards novel nanophotonic components via dense integration of large quantities of nonlinear resonators into compact metasurface designs.
Keywords: Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Potenziale und Grenzen von Unterstützungsmaßnahmen zum wissenschaftlichen Schreiben im Paderborner Physik Praktikum 3P - Bauer, Anna Brigitte; Lahme, Simon Zacharias; Sacher, Marc (PhyDid A - Physik und Didaktik in Schule und Hochschule)
Eines der Lernziele des Physikstudiums stellt der Erwerb literaler Fähigkeiten für das Verfassen wissenschaftlicher Arbeiten dar. Die Student:innen werden allerdings im Rahmen ihres Studiums bisher kaum systematisch beim Erwerb dieser Fähigkeiten unterstützt. Eine Übungsgelegenheit für das Verfassen von Texten nach wissenschaftlichem Vorbild stellt das Laborpraktikum dar, in dem die Student:innen zu den absolvierten Experimenten Laborberichte verfassen. Im Paderborner Physik Praktikum 3P wurden in den letzten Jahren vier unterschiedliche Unterstützungsangebote für das Erlernen des wissenschaftlichen Schreibens entwickelt und mittels Zufriedenheitswerten evaluiert. In dem Beitrag werden die vier Angebote auf inhaltlicher Ebene hinsichtlich der Lernwirksamkeit mittels einer schriftproduktbasierten Evaluation analysiert. Durch die vergleichende Analyse können Potenziale und Grenzen der Angebote diskutiert und Implikationen für die Gestaltung von Unterstützungsangeboten zum Erlernen des wissenschaftlichen Schreibens in der Physik abgeleitet werden.
Keywords: Laborpraktikum; Schreiben

Design and investigation of a metalens for efficiency enhancement of laser-waveguide coupling in a limited space system - laeim, Huddad; Schlickriede, Christian; Chaisakul, Papichaya; Chattham, Nattaporn; Panitchakan, Hathai; Siangchaew, Krisda; Zentgraf, Thomas; Pattanaporhratana, Apichart (Metamaterials, Metadevices, and Metasystems 2022)

Return to sports after ACL injury 5 years from now: 10 things we must do - Gokeler, Alli; Grassi, Alberto; Hoogeslag, Roy; van Houten, Albert; Bolling, Caroline; Buckthorpe, Matthew; Norte, Grant; Benjaminse, Anne; Heuvelmans, Pieter; Di Paolo, Stefano; Tak, Igor; Villa, Francesco Della (Journal of Experimental Orthopaedics)
Abstract Background The outcome after ACL reconstruction (ACLR) is in general disappointing with unacceptable number of athletes that do not return to pre-injury level of sports, high re-injury rates, early development of osteoarthritis and shorter careers. Athletes after ACLR have high expectation to return to sports which is in contrast with the current outcomes. The aim of this manuscript is to present an overview of factors that are needed to be incorporated and to personalize the rehabilitation process for an athlete who has undergone an ACLR. Level of evidence 4.
Keywords: Orthopedics and Sports Medicine

Cortical responses to sport-specific stimuli in a standing stop signal task - Scharfen, Hans-Erik; Lehmann, Tim; Büchel, Daniel; Baumeister, Jochen (Psychology of Sport and Exercise)
Keywords: Applied Psychology

Comparing lab and field agility kinematics in young talented female football players: Implications for ACL injury prevention - Di Paolo, Stefano; Nijmeijer, Eline; Bragonzoni, Laura; Dingshoff, Evelien; Gokeler, Alli; Benjaminse, Anne (European Journal of Sport Science)
Keywords: Orthopedics and Sports Medicine; Physical Therapy; Sports Therapy and Rehabilitation; General Medicine

Return to sports after ACL injury 5 years from now: 10 things we must do - Gokeler, Alli; Grassi, Alberto; Hoogeslag, Roy; van Houten, Albert; Lehman, Tim; Bolling, Caroline; Buckthorpe, Matthew; Norte, Grant; Benjaminse, Anne; Heuvelmans, Pieter; Di Paolo, Stefano; Tak, Igor; et al. (Journal of Experimental Orthopaedics)
Abstract Background The outcome after ACL reconstruction (ACLR) is in general disappointing with unacceptable number of athletes that do not return to pre-injury level of sports, high re-injury rates, early development of osteoarthritis and shorter careers. Athletes after ACLR have high expectation to return to sports which is in contrast with the current outcomes. The aim of this manuscript is to present an overview of factors that are needed to be incorporated and to personalize the rehabilitation process for an athlete who has undergone an ACLR. Level of evidence 4.
Keywords: Orthopedics and Sports Medicine

Correction: Return to sports after ACL injury 5 years from now: 10 things we must do - Gokeler, Alli; Grassi, Alberto; Hoogeslag, Roy; van Houten, Albert; Lehman, Tim; Bolling, Caroline; Buckthorpe, Matthew; Norte, Grant; Benjaminse, Anne; Heuvelmans, Pieter; Di Paolo, Stefano; Tak, Igor; et al. (Journal of Experimental Orthopaedics)
Keywords: Orthopedics and Sports Medicine

Comparing lab and field agility kinematics in young talented female football players: Implications for ACL injury prevention - Di Paolo, Stefano; Nijmeijer, Eline; Bragonzoni, Laura; Dingshoff, Evelien; Gokeler, Alli; Benjaminse, Anne (European Journal of Sport Science)
Keywords: Orthopedics and Sports Medicine; Physical Therapy; Sports Therapy and Rehabilitation; General Medicine

Genotype-phenotype mapping with polyominos made from DNA origami tiles - Dreher, Yannik; Fichtler, Julius; Karfusehr, Christoph; Jahnke, Kevin; Xin, Yang; Keller, Adrian; Göpfrich, Kerstin (Biophysical Journal)
Keywords: Biophysics

Enhanced corrosion resistance of epoxy-films on ultra-thin SiOx PECVD film coated laser surface melted Al-alloys - Varghese, J.; Vieth, P.; Xie, X.; Grundmeier, Guido (SN Applied Sciences)
Abstract The influence of ultra-thin SiO x plasma deposited films on the corrosion resistance of adhesive films on a laser surface melted 7075 aluminium alloy was investigated by means of complementary techniques in comparison to the just laser surface melted state. Laser surface melting (LSM) was performed using a continuous wave mode at a wavelength of 1064 nm. Ultra-thin plasma polymer films were deposited from a mixture of hexamethyldisilane (HMDSO), oxygen, and argon by means of an audio-frequency glow discharge. The surface morphology and surface chemistry compositions were investigated by employing field emission scanning electron microscopy, energy-dispersive X-ray spectroscopy (EDX), diffuse reflection infrared Fourier transform spectroscopy, and X-ray photoelectron spectroscopy. The corrosion resistance of plasma polymer coated LSM Al-7075 alloy was studied using linear sweep voltammetry and electrochemical impedance spectroscopy in a chloride-containing electrolyte. The electrochemical studies showed an improved corrosion resistance for plasma film-coated alloys compared to the just laser surface melted state. To study the corresponding surface adhesive properties, the samples were coated with an epoxy amine adhesive. 90°-peel test under humid conditions confirmed the improvement of interfacial wet-adhesion corrosion tests showed a strong improvement of the delamination resistance of adhesives caused by the ultra-thin interfacial SiO x -films.
Keywords: General Earth and Planetary Sciences; General Physics and Astronomy; General Engineering; General Environmental Science; General Materials Science; General Chemical Engineering

Influence of surface activation on the microporosity of PE‐CVD and PE‐ALD SiO x thin films on PDMS - Hoppe, Christian; Mitschker, Felix; Mai, Lukas; Liedke, Maciej Oskar; Arcos, Teresa; Awakowicz, Peter; Devi, Anjana; Attallah, Ahmed Gamal; Butterling, Maik; Wagner, Andreas; Grundmeier, Guido (Plasma Processes and Polymers)
Keywords: Polymers and Plastics; Condensed Matter Physics

High‐Resolution Study of Changes in Morphology and Chemistry of Cylindrical PS‐ b ‐PMMA Block Copolymer Nanomasks during Mask Development - Bürger, Julius; Venugopal, Harikrishnan; Kool, Daniel; de los Arcos, Teresa; Gonzalez Orive, Alejandro; Grundmeier, Guido; Brassat, Katharina; Lindner, Jörg K.N. (Advanced Materials Interfaces)
Keywords: General Medicine

Combined in-situ attenuated total reflection-Fourier transform infrared spectroscopy and single molecule force studies of poly(acrylic acid) at electrolyte/oxide interfaces at acidic pH - Neßlinger, Vanessa; Orive, Alejandro G.; Meinderink, Dennis; Grundmeier, Guido (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Comparative analysis of hexamethyldisiloxane and hexamethyldisilazane plasma polymer thin films before and after plasma oxidation - Xie, Xiaofan; de los Arcos, Teresa; Grundmeier, Guido (Plasma Processes and Polymers)
Keywords: Polymers and Plastics; Condensed Matter Physics

Ecological Validity in Exercise Neuroscience Research: A Systematic Investigation - Chang, M.; Büchel, Daniel; Reinecke, K.; Lehmann, T.; Baumeister, Jochen (European Journal of Neuroscience)
Keywords: General Neuroscience

The HSP40 chaperone Ydj1 drives amyloid beta 42 toxicity - Ring, Julia; Tadic, Jelena; Ristic, Selena; Poglitsch, Michael; Bergmann, Martina; Radic, Nemanja; Mossmann, Dirk; Liang, YongTian; Maglione, Marta; Jerkovic, Andrea; Hajiraissi, Roozbeh; Hanke, Marcel; et al. (EMBO Molecular Medicine)
Keywords: Molecular Medicine

Low Areal Densities of InAs Quantum Dots on GaAs(100) Prepared by Molecular Beam Epitaxy - Verma, A.K.; Bopp, F.; Finley, J.J.; Jonas, B.; Zrenner, A.; Reuter, Dirk (Journal of Crystal Growth)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

Experimental verification of the acoustic geometric phase - Liu, Bingyi; Zhou, Zhiling; Wang, Yongtian; Zentgraf, Thomas; Li, Yong; Huang, Lingling (Applied Physics Letters)
Optical geometric phase encoded by in-plane spatial orientation of microstructures has promoted the rapid development of numerous functional meta-devices. However, pushing the concept of the geometric phase toward the acoustic community still faces challenges. In this work, we utilize two acoustic nonlocal metagratings that could support a direct conversion between an acoustic plane wave and a designated vortex mode to obtain the acoustic geometric phase, in which an orbital angular momentum conversion process plays a vital role. In addition, we realize the acoustic geometric phases of different orders by merely varying the orientation angle of the acoustic nonlocal metagratings. Intriguingly, according to our developed theory, we reveal that the reflective acoustic geometric phase, which is twice the transmissive one, can be readily realized by transferring the transmitted configuration to a reflected one. Both the theoretical study and experimental measurements verify the announced transmissive and reflective acoustic geometric phases. Moreover, the reconfigurability and continuous phase modulation that covers the 2π range shown by the acoustic geometric phases provide us with the alternatives in advanced acoustic wavefront control.
Keywords: Physics and Astronomy (miscellaneous)

Giant Photoelasticity of Polaritons for Detection of Coherent Phonons in a Superlattice with Quantum Sensitivity - Kobecki, Michal; Scherbakov, Alexey V.; Kukhtaruk, Serhii M.; Yaremkevich, Dmytro D.; Henksmeier, Tobias; Trapp, Alexander; Reuter, Dirk; Gusev, Vitalyi E.; Akimov, Andrey V.; Bayer, Manfred (Physical Review Letters)
Keywords: General Physics and Astronomy

Anion-specific structure and stability of guanidinium-bound DNA origami - Hanke, Marcel; Dornbusch, Daniel; Hadlich, Christoph; Rossberg, Andre; Hansen, Niklas; Grundmeier, Guido; Tsushima, Satoru; Keller, Adrian; Fahmy, Karim (Computational and Structural Biotechnology Journal)
Keywords: Computer Science Applications; Genetics; Biochemistry; Structural Biology; Biophysics; Biotechnology

Combined Effects of Uniform Applied Pressure and Electrolyte Additives in Lithium-Metal Batteries - Kasse, Robert M.; Geise, Natalie R.; Sebti, Elias; Lim, Kipil; Takacs, Christopher J.; Cao, Chuntian; Steinrück, Hans-Georg; Toney, Michael F. (ACS Applied Energy Materials)
Keywords: Electrical and Electronic Engineering; Materials Chemistry; Electrochemistry; Energy Engineering and Power Technology; Chemical Engineering (miscellaneous)

Direct visualization of the drug loading of single DNA origami nanostructures by AFM-IR nanospectroscopy - Hanke, Marcel; Grundmeier, Guido; Keller, Adrian (Nanoscale)
The efficient loading of DNA nanostructures with intercalating or groove-binding drugs is an important prerequisite for various applications in drug delivery. However, unambiguous verification and quantification of successful drug loading...
Keywords: General Materials Science

Dietary protein intake and health-related outcomes: a methodological protocol for the evidence evaluation and the outline of an evidence to decision framework underlying the evidence-based guideline of the German Nutrition Society - Kroke, Anja; Schmidt, Annemarie; Amini, Anna M.; Kalotai, Nicole; Lehmann, Andreas; Haardt, Julia; Bauer, Jürgen M.; Bischoff-Ferrari, Heike A.; Boeing, Heiner; Egert, Sarah; Ellinger, Sabine; Kühn, Tilman; et al. (European Journal of Nutrition)
Abstract Purpose The present work aimed to delineate (i) a revised protocol according to recent methodological developments in evidence generation, to (ii) describe its interpretation, the assessment of the overall certainty of evidence and to (iii) outline an Evidence to Decision framework for deriving an evidence-based guideline on quantitative and qualitative aspects of dietary protein intake. Methods A methodological protocol to systematically investigate the association between dietary protein intake and several health outcomes and for deriving dietary protein intake recommendations for the primary prevention of various non-communicable diseases in the general adult population was developed. Results The developed methodological protocol relies on umbrella reviews including systematic reviews with or without meta-analyses. Systematic literature searches in three databases will be performed for each health-related outcome. The methodological quality of all selected systematic reviews will be evaluated using a modified version of AMSTAR 2, and the outcome-specific certainty of evidence for systematic reviews with or without meta-analysis will be assessed with NutriGrade. The general outline of the Evidence to Decision framework foresees that recommendations in the derived guideline will be given based on the overall certainty of evidence as well as on additional criteria such as sustainability. Conclusion The methodological protocol permits a systematic evaluation of published systematic reviews on dietary protein intake and its association with selected health-related outcomes. An Evidence to Decision framework will be the basis for the overall conclusions and the resulting recommendations for dietary protein intake.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Einbettung von Augmented Reality in den Experimentierprozess - Peeters, Hendrik; Habig, Sebastian; Fechner, Sabine (Unsicherheit als Element von naturwissenschaftsbezogenen Bildungsprozessen)
Keywords: augmented reality; modelle; digitale Medien

Quantum Dot Molecule Devices with Optical Control of Charge Status and Electronic Control of Coupling - Bopp, Frederik; Rojas, Jonathan; Revenga, Natalia; Riedl, Hubert; Sbresny, Friedrich; Boos, Katarina; Simmet, Tobias; Ahmadi, Arash; Gershoni, David; Kasprzak, Jacek; Ludwig, Arne; Reitzenstein, Stephan; et al. (Advanced Quantum Technologies)
Keywords: Electrical and Electronic Engineering; Computational Theory and Mathematics; Condensed Matter Physics; Mathematical Physics; Nuclear and High Energy Physics; Electronic; Optical and Magnetic Materials; Statistical and Nonlinear Physics

Correction to: Changes in patterns of eating habits and food intake during the first German COVID-19 lockdown: results of a cross-sectional online survey - Bühlmeier, Judith; Frölich, Stefanie; Ludwig, Christine; Knoll-Pientka, Nadja; Schmidt, Börge; Föcker, Manuel; Libuda, Lars (European Journal of Nutrition)
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Age at menarche relates to depression in adolescent girls: Comparing a clinical sample to the general pediatric population - Hirtz, Raphael; Libuda, Lars; Hinney, Anke; Föcker, Manuel; Bühlmeier, Judith; Holterhus, Paul-Martin; Kulle, Alexandra; Kiewert, Cordula; Kuhnert, Ronny; Cohrdes, Caroline; Peters, Triinu; Hebebrand, Johannes; et al. (Journal of Affective Disorders)
Keywords: Psychiatry and Mental health; Clinical Psychology

Second-harmonic generation in atomically thin 1T−TiSe2 and its possible origin from charge density wave transitions - Zhang, Ruiming; Ruan, Wei; Yu, Junyao; Gao, Libo; Berger, Helmuth; Forró, László; Watanabe, Kenji; Taniguchi, Takashi; Ranjbar, Ahmad; Belosludov, Rodion V.; Kühne, Thomas; Bahramy, Mohammad Saeed; et al. (Physical Review B)

Electronic Structures of Group III–V Element Haeckelite Compounds: A Novel Family of Semiconductors, Dirac Semimetals, and Topological Insulators - Khazaei, Mohammad; Ranjbar, Ahmad; Kang, Yoon‐Gu; Liang, Yunye; Khaledialidusti, Rasoul; Bae, Soungmin; Raebiger, Hannes; Wang, Vei; Han, Myung Joon; Mizoguchi, Hiroshi; Bahramy, Mohammad S.; Kühne, Thomas; et al. (Advanced Functional Materials)
Keywords: Electrochemistry; Condensed Matter Physics; Biomaterials; Electronic; Optical and Magnetic Materials

Real-Space Identification of Non-Noble Single Atomic Catalytic Sites within Metal-Coordinated Supramolecular Networks - Schulze Lammers, Bertram; López-Salas, Nieves; Stein Siena, Julya; Mirhosseini, Hossein; Yesilpinar, Damla; Heske, Julian Joachim; Kühne, Thomas; Fuchs, Harald; Antonietti, Markus; Mönig, Harry (ACS Nano)
Keywords: General Physics and Astronomy; General Engineering; General Materials Science

On the Role of Hydrogen Bond Strength and Charge Transfer of a Diels-Alder Reaction On-Water: Semiempirical and Free Energy Calculations. - Henao Aristizabal, Andres; Gohar, Yomna; Whilhelm, René; Kühne, Thomas
Accelerated chemistry at the interface with water has received increasing attention. The mechanisms behind the enhanced reactivity On-Water are not yet clear. In this work we use a Langevin scheme in the spirit of second generation Car-Parrinello to accelerate the second-order density functional Tight-Binding (DFTB2) method in order to investigate the free energy of two Diels-Alder reaction On-Water: the cycloaddition between cyclopentadiene and ethyl cinnamate or thionocinnamate. The only difference between the reactants is the substitution of a carbonyl oxygen for a thiocarbonyl sulfur, making possible the distinction between them as strong and weak hydrogen-bond acceptors. We find a different mechanism for the reaction during the transition states and uncover the role of hydrogen bonds along with the reaction path. Our results suggest that acceleration of Diels-Alder reactions do not arise from an increased number of hydrogen bonds at the transition state and charge transfer plays a significant role. However, the presence of water and hydrogen-bonds is determinant for the catalysis of these reactions.

CENT2: Improved charge equilibration via neural network technique - Khajehpasha, Ehsan Rahmatizad; Finkler, Jonas A.; Kühne, Thomas; Ghasemi, Alireza (Physical Review B)

Surface Passivation and Detrimental Heat-Induced Diffusion Effects in RbF-Treated Cu(In,Ga)Se2 Solar Cell Absorbers - Elizabeth, Amala; Sahoo, Sudhir K.; Phirke, Himanshu; Kodalle, Tim; Kühne, Thomas; Audinot, Jean-Nicolas; Wirtz, Tom; Redinger, Alex; Kaufmann, Christian A.; Mirhosseini, Hossein; Mönig, Harry (ACS Applied Materials & Interfaces)
Keywords: General Materials Science

Fingerprints Indicating Superior Properties of Internal Interfaces in Cu(In,Ga)Se 2 Thin‐Film Solar Cells - Raghuwanshi, Mohit; Chugh, Manjusha; Sozzi, Giovanna; Kanevce, Ana; Kühne, Thomas; Mirhosseini, Hossein; Wuerz, Roland; Cojocaru‐Mirédin, Oana (Advanced Materials)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Do Lead Halide Hybrid Perovskites Have Hydrogen Bonds? - Ibaceta-Jaña, Josefa; Chugh, Manjusha; Novikov, Alexander S.; Mirhosseini, Hossein; Kühne, Thomas; Szyszka, Bernd; Wagner, Markus R.; Muydinov, Ruslan (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Ni-based electrocatalysts for unconventional CO2 reduction reaction to formic acid - Lepre, Enrico; Heske, Julian Joachim; Nowakowski, Michal; Scoppola, Ernesto; Zizak, Ivo; Heil, Tobias; Kühne, Thomas; Antonietti, Markus; López-Salas, Nieves; Albero, Josep (Nano Energy)
Keywords: Electrical and Electronic Engineering; General Materials Science; Renewable Energy; Sustainability and the Environment

Time resolved THz-Raman spectroscopy reveals that cations and anions distinctly modify intermolecular interactions of water - Balos, Vasileios; Kaliannan, Naveen Kumar; Elgabarty, Hossam; Wolf, Martin; Kühne, Thomas; Sajadi, Mohsen

Giant Orbital Anisotropy with Strong Spin–Orbit Coupling Established at the Pseudomorphic Interface of the Co/Pd Superlattice - Kim, Sanghoon; Pathak, Sachin; Rhim, Sonny H.; Cha, Jongin; Jekal, Soyoung; Hong, Soon Cheol; Lee, Hyun Hwi; Park, Sung‐Hun; Lee, Han‐Koo; Park, Jae‐Hoon; Lee, Soogil; Steinrück, Hans-Georg; et al. (Advanced Science)
Keywords: General Physics and Astronomy; General Engineering; Biochemistry; Genetics and Molecular Biology (miscellaneous); General Materials Science; General Chemical Engineering; Medicine (miscellaneous)

PTBP2 – a gene with relevance for both Anorexia nervosa and body weight regulation - Zheng, Yiran; Rajcsanyi, Luisa Sophie; Herpertz-Dahlmann, Beate; Seitz, Jochen; de Zwaan, Martina; Herzog, Wolfgang; Ehrlich, Stefan; Zipfel, Stephan; Giel, Katrin; Egberts, Karin; Burghardt, Roland; Föcker, Manuel; et al. (Translational Psychiatry)
Abstract Genetic factors are relevant for both eating disorders and body weight regulation. A recent genome-wide association study (GWAS) for anorexia nervosa (AN) detected eight genome-wide significant chromosomal loci. One of these loci, rs10747478, was also genome-wide and significantly associated with body mass index (BMI). The nearest coding gene is the Polypyrimidine Tract Binding Protein 2 gene ( PTBP2 ). To detect mutations in PTBP2 , Sanger sequencing of the coding region was performed in 192 female patients with AN (acute or recovered) and 191 children or adolescents with (extreme) obesity. Twenty-five variants were identified. Twenty-three of these were predicted to be pathogenic or functionally relevant in at least one in silico tool. Two novel synonymous variants (p.Ala77Ala and p.Asp195Asp), one intronic SNP (rs188987764), and the intronic deletion (rs561340981) located in the highly conserved region of PTBP2 may have functional consequences. Ten of 20 genes interacting with PTBP2 were studied for their impact on body weight regulation based on either previous functional studies or GWAS hits for body weight or BMI. In a GWAS for BMI (Pulit et al. 2018), the number of genome-wide significant associations at the PTBP2 locus was different between males (60 variants) and females (two variants, one of these also significant in males). More than 65% of these 61 variants showed differences in the effect size pertaining to BMI between sexes (absolute value of Z -score >2, two-sided p < 0.05). One LD block overlapping 5′UTR and all coding regions of PTBP2 comprises 56 significant variants in males. The analysis based on sex-stratified BMI GWAS summary statistics implies that PTBP2 may have a more pronounced effect on body weight regulation in males than in females.
Keywords: Biological Psychiatry; Cellular and Molecular Neuroscience; Psychiatry and Mental health

Changes in patterns of eating habits and food intake during the first German COVID-19 lockdown: results of a cross-sectional online survey - Bühlmeier, Judith; Frölich, Stefanie; Ludwig, Christine; Knoll-Pientka, Nadja; Schmidt, Börge; Föcker, Manuel; Libuda, Lars (European Journal of Nutrition)
Abstract Purpose The COVID-19 pandemic and public measures have a direct impact on the nutrition situation; studies show changes in food consumption, eating behavior or body weight but complex pattern analyses of changes rarely exist. Methods During the first German lockdown, a web-based survey was conducted among adults. It included 33 questions about changes in food intake, eating habits and physical activity, as well as anthropometrics and sociodemographic factors. Patterns of change were calculated based on changes in food intake and eating habits using two-step cluster analysis. To identify influencing factors for assignment to the patterns of change, binary logistic regression analyses were performed. Results Data from 2103 participants (81% female, 40 ± 14 years) were considered for analysis. Increased stockpiling, cooking, and variation in preparation was reported by 50–70%. The constant pattern (C-P, 36%) reported little change besides the above. The health-oriented pattern (HO-P; 37%) reported eating more healthy foods, avoiding unhealthy foods, and eating less and less frequently. The emotional-driven pattern (ED-P; 28%) exhibits higher influence of emotions on eating behavior, less avoidance of unhealthy foods, and increased consumption of sweets, pastries, and alcohol. The odds of changing eating behavior either to HO-P or ED-P were higher in women, people with migration background, younger participants, and increased with BMI categories. Conclusion Both, the ED-P and HO-P, exhibit distinctive reactions in eating habits and food intake when dealing with a distressing experience. In subgroups, these may lead to disturbances in eating behavior and increase the risk for eating disorders and obesity.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Prospective association of family members’ sugar-sweetened beverages intake with children’s sugar-sweetened beverages consumption in China - Liu, Xue-Ting; Xiong, Jing-Yuan; Xu, Yu-Jie; Zhao, Li; Libuda, Lars; Cheng, Guo (European Journal of Nutrition)
Abstract Purpose We aimed to investigate whether parental and siblings’ sugar-sweetened beverage (SSB) intake had prospective impact on children’s SSB consumption, and the potential sex difference in these associations. Methods This study included a total of 904 children and their parents enrolled from 2004 to 2011 China Health and Nutrition Survey (CHNS) cohort study. SSB consumption information was estimated using a short dietary questionnaire and total energy intake was assessed with three-day 24-h dietary assessments at recruitment and follow-up surveys. Multivariate logistic or linear regression analyses were used to assess the association for SSB consumption between parents, siblings and children after adjusting for age, body mass index (BMI) z -score, household income and parental educational level. Results In this study, a majority (87.6%) of children consumed SSB. Among them, the median consumption of SSB was 70.3 ml/day per capita and 205.4 ml/day per consumer. Parental SSB consumption was relevant to children’s SSB consumption, and this association was more pronounced in boys than in girls. Meanwhile, fathers seemed to have a stronger impact on whether children consume SSB than mothers which was reflected by lower P and higher OR. Additionally, children’s SSB intake was prospectively associated with their older siblings’ SSB consumption ( P for trend < 0.03). Conclusions Parental and older siblings’ SSB consumption was relevant to children’s SSB intake. Particularly, boys were more susceptible to parental impact than girls, and fathers seemed to have a greater influence on children than mothers.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Towards new nutritional policies for brain health: A research perspective on future actions - Adan, Roger A.H.; Cirulli, Francesca; Dye, Louise; Higgs, Suzanne; Aarts, Kristien; van der Beek, Eline M.; Buitelaar, Jan K.; Destrebecq, Frédéric; De Witte, Elke; Hartmann, Tobias; Korosi, Aniko; Libuda, Lars; et al. (Brain, Behavior, and Immunity)
Keywords: Behavioral Neuroscience; Endocrine and Autonomic Systems; Immunology

Low leptin levels are associated with elevated physical activity among lean school children in rural Tanzania - Ludwig, Christine; Knoll-Pientka, Nadja; Mwanri, Akwilina; Erfle, Celina; Onywera, Vincent; Tremblay, Mark S.; Bühlmeier, Judith; Luzak, Agnes; Ferland, Maike; Schulz, Holger; Libuda, Lars; Hebebrand, Johannes (BMC Public Health)
Abstract Background In Sub-Saharan African countries, rapid urbanization and increasing socio-economic status are associated with a transition to decreased physical activity (PA). A more sedentary lifestyle is linked to increased body fat leading to increments in leptin levels. Since rodent and human studies in high-income countries have shown that starvation-induced hypoleptinemia triggers high PA, efforts are warranted to pursue the hypothesis that low leptin levels in lean children of low- and middle-income countries (LMIC) are also associated with high PA. Methods In this cross-sectional study, we assessed seven-day PA with triaxial accelerometry (ActiGraph GT3X) among 223 primary school children (9 to 12 years of age) in rural Tanzania. Moderate-to-vigorous PA (MVPA) and total accelerometer counts per day were outcome variables. Leptin was determined using enzyme linked immunosorbent assay tests from dried blood spots. Anthropometric assessments were conducted and food insecurity and socio-demographic data were gathered using semi-structured interviews. Results In this sample of school children in rural Tanzania, leptin concentrations (median: 0.91 ng/mL, P25: 0.55, P75: 1.69), body mass index z-scores (median: -1.35, P25: -1.93, P75: -0.82), and height-for-age-z-scores (median: -1.16, P25: -1.96, P75: -0.61) were low. In contrast, PA levels were high with a median MVPA time of 119 min/day. Linear regression confirmed that leptin levels were negatively associated with MVPA (beta: -18.1; 95%CI: -29.7; -6.5; p = 0.002) and total accelerometer counts (beta: -90,256; 95%CI: -154,146; -26,365; p = 0.006). Children residing in areas with better infrastructure had lower MVPA levels ( p < 0.001) and tended to have higher leptin levels ( p = 0.062) than children residing in areas only reachable via dirt roads. Conclusion Our cross-sectional field study is the first that supports the hypothesis of low leptin levels as a potential endocrine trigger of high PA in lean children of a LMIC. We observed early signs of a PA transition towards a less active lifestyle in a subgroup residing in areas with better infrastructure that concomitantly tended to have higher leptin concentrations. Considering that area-dependent PA differences were more pronounced among girls than boys, whereas differences in leptin levels were less pronounced, not only biological, but also external factors explain PA transition.
Keywords: Public Health; Environmental and Occupational Health